Anmeldelser - Woetmann Christoffersen, Peter (Danish Yearbook of Musicology, 2017)
Review of: John Bergsagel, David Hiley and Thomas Riis (eds.): Of Chronicles and Kings. National Saints and the Emergence of Nation States in the High Middle Ages. Danish Humanist Texts and Studies, 52. Copenhagen: Museum Tusculanum Press, 2016